2010
DOI: 10.4028/www.scientific.net/amr.163-167.32
|View full text |Cite
|
Sign up to set email alerts
|

Research on Ultimate Bearing Capacity of Coupler Steel Tube Falsework with Initial Defect

Abstract: Used of finite element software, based on the material characteristic and node semi-rigid experimentations, the model with material multi-linear kinematic hardening and node semi-rigid was established to simulate the test model of coupler steel tube falsework. According to the measured data of the defect, to analyze the nonlinear stability of the model by methods of the consistent defect mode and stochastic defect, the results indicate that the model’s correctness and consistent mode imperfection method’s in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Recent research in China has been undertaken on theoretical and experimental models of tube-and-fitting scaffolds. Hu et al [79][80][81] undertook experiments on scaffold assemblies and showed that when the imperfections in the scaffold were correctly modeled that correspondence was made with analytical models. Li et al [82] developed a semiempirical design tool for the analysis of scaffolds and compared the results with a finite element program with good correlation.…”
Section: Tube-and-fitting Modelsmentioning
confidence: 99%
“…Recent research in China has been undertaken on theoretical and experimental models of tube-and-fitting scaffolds. Hu et al [79][80][81] undertook experiments on scaffold assemblies and showed that when the imperfections in the scaffold were correctly modeled that correspondence was made with analytical models. Li et al [82] developed a semiempirical design tool for the analysis of scaffolds and compared the results with a finite element program with good correlation.…”
Section: Tube-and-fitting Modelsmentioning
confidence: 99%